ER/LA Opioid Analgesics REMS: Overview of Ongoing Assessments of Its Progress and Its Impact on Health Outcomes - Cepeda, M. Soledad (Pain Med, 2017)
Objective. Opioid abuse is a serious public health concern. In response, the Food and Drug Administration (FDA) determined that a risk evaluation and mitigation strategy (REMS) for extended-release and long-acting (ER/LA) opioids was necessary to ensure that the benefits of these analgesics continue to outweigh the risks. Key components of the REMS are training for prescribers through accredited continuing education (CE), and providing patient educational materials. Methods. The impact of this REMS has been assessed using diverse metrics including evaluation of prescriber and patient understanding of the risks associated with opioids; patient receipt and comprehension of the medication guide and patient counseling document; patient satisfaction with access to opioids; drug utilization and changes in prescribing patterns; and surveillance of ER/LA opioid misuse, abuse, overdose, addiction, and death. Results and Conclusions. The results of these assessments indicate that the increasing rates of opioid abuse, addiction, overdose, and death observed prior to implementation of the REMS have since leveled off or started to decline. However, these benefits cannot be attributed solely to the ER/LA opioid analgesics REMS since many other initiatives to prevent abuse occurred contemporaneously. These improvements occurred while preserving patient access to opioids as a large majority of patients surveyed expressed satisfaction with their access to opioids.